Accounting & auditing research and databases : practitioner's desk reference - Weirich, Thomas R.; Churyk, Natalie T.; Pearson, Thomas C. (Hoboken, N.J. : Wiley, 2012)
The easy-to-use, do-it-yourself desk accounting and auditing research database FASB's online GAAP Codification system. The convergence of U.S. GAAP and International Financial Reporting Standards. EDGAR filing and research system. RIA Checkpoint and CCH. Accounting professionals and practitioners need to understand these research databases to reach solutions and achieve maximum results for the organization. Highlighting each pertinent database, Accounting and Auditing Research Databases shows you how to conduct research using a host of databases including RIA, CCH, AICPA's Online Libr.
Chapter 3: The Environment of International ResearchThe International Accounting Environment; International Accounting Standards Board (IASB); Other Regional and National Standard-Setting Bodies and Organizations Influencing IFRS; IASB Authorities; IASB Due Process; Interpretations Committee Due Process; The IASB's Conceptual Framework; IFRS Funding, Regulation, and Enforcement; International Financial Reporting Standards (IFRS) Research; IFRS Hierarchy; eIFRS Access; Entering eIFRS; The IFRS Research Process; Print and Copy/Paste functions; Summary; Notes
Includes bibliographical references and index.
Keywords: Accounting -- Research; Auditing -- Research; Accounting -- Data processing; Auditing -- Data processing; BUSINESS & ECONOMICS / Accounting / Financial